Comparative Chinese personal’s Affixes and Indonesian personal’s Affixes - Sunarti Sunarti; Karina Fefi Laksana Sakti (Makassar State University, 2020)
This paper compares and analyzes Chinese personal’s Affixes and Indonesian personal’s Affixes. The research method uses qualitative interpretation. Sequential steps are used (1) Identification, (2) classification, (3) comparative data, (4) verification data, (5) description of results, and discussion of presentation (6) conclusion. This paper found that the Indonesian personal Affixess and the Chinese personal Affixess are not completely one-to-one correspondence, and there is a one-to-many and one-to-one relationship. Example: one to many relationships is pe- similar to 师、生、家、者、员、星 and 张. One to one relationship is –wan similar to 家. Similarly, Chinese personal Affixess and Indonesian personal Affixes are not completely one-to-one correspondences, with a one-to-two and one-to-one relationship. Example: one to many relationships is 者- similar to pe- and -wan. One to one relationship is 师similar with pe-.